International Electron Devices Meeting 1998. Technical Digest (Cat. No.98CH36217)
DOI: 10.1109/iedm.1998.746342
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen degradation in InP HEMTs

Abstract: Hydrogen degradation is a serious reliability concern for III-V FETs. Exposure can occur when hydrogen out-gasses from packaging material and becomes trapped inside hermetically sealed packages. The detailed mechanism by which H2 degrades FETs is not understood and a device-level solution to this problem has not been reported.This work investigates the hydrogen degradation of InP High-Electron-Mobility Transistors (HEMTs) fabricated at MIT. We show that there are three independent degradation mechanisms: two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Here, the forward-biased gate current increases significantly and the parasitic resistances decreases. Previous observations of the H-induced piezoelectric effect did not show any H-induced changes in the Schottky-barrier height[37].…”
contrasting
confidence: 54%
“…Here, the forward-biased gate current increases significantly and the parasitic resistances decreases. Previous observations of the H-induced piezoelectric effect did not show any H-induced changes in the Schottky-barrier height[37].…”
contrasting
confidence: 54%
“…The reduction of required to realize the increase in could occur through donor passivation [3], through changes in the surface in the extrinsic region [10], [11], or through stress-induced piezoelectric charges in the extrinsic region [1], [2]. Previous work has shown that exposure to H leads to compressive stress in Ti/Pt/Au gates due to the formation of TiH [1], [2] and the creation of a piezoelectric volume charge distribution in the device. Piezoelectric charge is ruled out here as the main cause of the decrease because there is no orientation dependence to .…”
Section: Resultsmentioning
confidence: 99%
“…Over time, hydrogen causes changes in device characteristics that can ultimately lead to parametric module failures. Compared with more extensive studies of H degradation of GaAs MESFETs and PHEMTs [3]- [6], only limited data on the H sensitivity of InP HEMTs is available [1], [2], [5]. To our knowledge, a device-level solution to this problem has not been reported for either InP or GaAs technologies.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations